ARSITEKTUR BANGUNAN RUMAH TRADISIONAL JAWA: KEBERADAAN BANGUNAN TRADISIONAL JAWA DI KAMPUNG KAUMAN, YOGYAKARTA - Muhammad Chawari (BRIN, 1999)
The existence of Kauman Village cannot be separated from the history and establishment of the Islamic Mataram Kingdom in the last period (starting from the Hamengku Buwana dynasty). In addition, Kauman is a part of the Mataram Kingdom bureaucracy. Several years after this kingdom was founded, it began to develop a place of worship (mosque). Finally, the building of this large mosque stood about 18 years after Prince Mangkubumi was inaugurated as a sultan with the title Sri Sultan Hamengkubuwana I. After this mosque was established, the kingdom then placed a royal ruler, a